HUBUNGAN FAKTOR LINGKUNGAN DENGAN KEJADIAN PENYAKIT DEMAM BERDARAH DENGUE DBD DI WILAYAH PUSKESMAS CIPONDOH TAHUN 2022 - Putri Amelia; Hyang Wreksagung; Zahra Maulidia Septimar (Nusantara Hasana Journal, 2022)
Dengue hemorrhagic fever is an environmental infection, meaning that the environment plays an important role in disease transmission. Objective to determine the relationship between environmental factors and the incidence of DHF. This study was conducted with a descriptive research design with a cross sectional approach, used to review the dynamics of the relationship with risk factors with effects in the form of health problems or certain health statuses. Based on research after the Chi Square test there is a value of 3 cells (0.0%), there is an Expectet Count value <0.05, it is known that the significant value of the relationship between environmental factors and the incidence of dengue hemorrhagic fever (DHF) in the Cipondoh Health Center area is P -Value (<0.003) then Ha is accepted, which means that there is a relationship between environmental factors and the incidence of DHF. There is a relationship between environmental factors and the incidence of DHF in the Cipondoh Public Health Center, Tangerang.